Phenology of the jobo (Spondias mombin L.) (Agro Productividad, 2026)
Objective: To identify the flowering and fruiting periods of the species by examining the correlation between climate conditions and phenophases. Design/Methodology/Approach: Spondias mombin L. is an underutilized species with minimal or no management. An edaphoclimatic characterization of the study area was conducted, along with an assessment of its vulnerability to climate change. Botanical identification of the species and its main propagation methods were also performed. Additionally, temperature and precipitation data for the year 2021 were analyzed, enabling a phenological evaluation. Results: Full flowering occurred between April and May, while fruit ripening progressed gradually throughout July and August. Defoliation was linked to a decline in temperatures during November and December, marking the onset of the dormant phase. The phenology of S. mombinexhibited variability in its phenophases depending on the specific environmental conditions of its habitat, particularly during the fruit ripening stage. The individuals studied showed asynchronous phenological patterns, with flowering and fruiting occurring at different times. Limitations/Implications: This study faces certain limitations, including its local scope, climatic variability, and a limited number of samples. Findings/Conclusions: Although this study provides valuable insights into the phenology of Spondias mombin, further research is essential to deepen the understanding of how climate change influences this species and to assess its potential for agroforestry applications.